Myasthenia Gravis in an Exotic Shorthair Cat - Macedo, Aline Schafrum [UNESP]; Silva, Renato Barbosa; Fett, Rochana Rodrigues; Minto, Bruno Watanabe [UNESP] (Univ Fed Rio Grande Do Sul, 2015)
Background: Myasthenia gravis is a neuromuscular transmission disorder resulting from the deficiency or functional disturbance of the acetylcholine receptors at the neuromuscular junction with consequent impairment of action potential transmission from nerve to muscle and it can be either congenital or acquired. Acquired myasthenia gravis has been described less frenquently in cats. The purpose of this paper is to describe a case of acquired myasthenia gravis in a 6-month-old male Exotic Shorthair cat. Case: A 6-month-old male Exotic Shorthair cat was referred to the Veterinary Clinic with a 2-day history of flaccid paralysis of the four limbs. The cat was feeding well and defecating normally. Physical examination was unremarkable. On neurological examination the patient was bright, alert and responsive. Flaccid paralysis of the four limbs was evident with loss of muscular tonus and presence of superficial and deep nociception. All spinal reflexes were absent. Hematologic analysis was within normal parameters. Thoracic radiographs were taken and showed no abnormalities. Creatine kinase activity was elevated. Myasthenia gravis was suspected and the cat was submitted to an neostigmine methylsulfate injection and further pyridostigmine bromide administration. Within 15 days there was clinical improvement with muscular tonus and spinal reflexes recovery. The treatment was continued for 3 months. On follow ups the cat showed improvement in clinical signs. After the medication withdrawn, the cat didn't show any of the disease's symptoms. Discussion: Myasthenia gravis (MG) is characterized by muscle weakness, explained by the presence of T cell-dependent antibodies to the nicotinic acetylcholine receptors (AChRs) of the postsynaptic membrane in the neuromuscular junction. The nicotinic AChRs play a fundamental role on the neuromuscular transmission and any disturbance on these structures can interfere on muscle contracture and cause weakness due to the impairment of action potential transmission from nerve to muscle. Based on clinical finds and the satisfactory response to neostigmine metilsulfate and pyridostigmine bromide, presumptive diagnostic of MG was confirmed. Autoimmune MG can occur spontaneously in dogs and has been extensively studied and classified as analogous to the human form; although it is also spontaneous in cats, it is a rare condition and few reports are available. The treatment with pyridostigmine bromide was effective and helped on the diagnosis. Anticholinesterase drugs are the treatment of choice for MG because they act prolonging the action of acetylcholine at the neuromuscular junction. The occurrence of megaesophagus in cats is lower than in dogs and the manifestation of MG with a mediastinal mass is higher in cats. No mediastinal masses were present in this case. The cat was an Exotic Shorthair. There is a known relative risk for acquired MG in Abyssinian and Somali cats and, it has been reported in Persians, the closest breed to Exotics. The differential diagnoses to be considered are other disorders of neuromuscular transmission such as congenital MG, botulism, polymyositis, polyneuropathy, organophosphate toxicity, hypoadrenocorticism and hypothyroidism. Autoimmune MG is an important neuromuscular dysfunction that should be considered as differential diagnosis for cats with muscle weakness. Early diagnosis and treatment are decisive and should be used for a better prognosis.
Keywords: flaccid paralysis; acetylcholine; neuromuscular disorder; feline